Pyogenic Spondylodiscitis due to Streptococcus constellatus in an Immunocompromised Male Patient: A Case Report and Review of the Literature - Charalampos Potsios; Panagiota Xaplanteri; Vasileios Zoitopoulos; Panagiotis Patrinos; Iro Ioanna Giannakopoulou; Ilektra Tzivaki; Theodora Kafentzi; Konstantina Samanta; Konstantina Filioti; Panagiotis Sideris; Konstantinos Letsas; Konstantinos Koukios (Case Reports in Infectious Diseases)
Pyogenic spondylodiscitis is a primary infection of the intervertebral disc and is a rare entity. Here, we describe the case of a 64-year-old male patient, a professional breeder, who attended the Emergency Department with sciatica and back pain that was worsening for a week. The patient had no history of surgery or trauma. The patient had poor oral hygiene. Magnetic resonance imaging (MRI) scan showed lumbar spondylodiscitis, and blood cultures revealed Streptococcus constellatus. The patient was initially treated with vancomycin but due to renal failure deterioration, the treatment was changed to daptomycin for 8 weeks. During hospitalization, he endured renal injury and nosocomial respiratory tract infection. The patient was discharged with no further complications. Follow-up revealed improvement of neurological signs. In our case, it seems that poor oral hygiene was the cause of bacteremia, which underlies the importance of a good oral health status in immunocompromised patients not only to prevent but also to successfully eliminate any dental source of infection. S. constellatus is an extremely rare pathogen and to our knowledge only two other cases of pyogenic spondylodiscitis are reported in the literature. Early diagnosis is very important for the prognosis of these patients.